Tafsir Sufistik Nusantara - Usep Taufik Hidayat (LP2M STAI Al-Muhajirin Purwakarta, 2021)
This short article will tell us about Sufism Aspect in Tafsir Nusantara. It's about the sufistic pattern in tafsir (lawn al-shufy). Tafsir Nusantara accorded toIsamic Scholars 's view is an quranic interpretaion wrote by mufassir with Indonesian nationality. This article is one of answers and my opinion given to all readers in order to get sighting to esoteric quranic interpretation. We always find essays say about the decrease of spiritual in urban and big city peoples. Althoght this article does not diagnose the fluctuative of that directly, but at least the substance of verses which interprated will give enlighment for our soul. On my opinion, Sheikh Nawawi had a qualified interpretation in sufistic pattern . We must have understood itfrom the title of his book, Maraah Labid Fi Tafsir Quranim Majid. It imagines it's author wants to tell us that his work can give the readers many informations about religious affair as the list of religious tourism destinations which stimulate to our activities, despite limited by methodology and writing system. Sheikh Ihsan with his magnum opus Siraj al-Thalibin could diagnose the weak spiritual and mystical that spread in his environment. He took the Greatest Islamic philosop thinker Al-Ghazali's work , Minhaj al-Abidin as a docter prescription for treatment. Muhammad Quraish Shihab interprates them progressively. He had completed the sufistic patern in quranic interpretation by early saintific approaches. This acarticle is purposed to know sufism aspect at all those books, through taking 2 essential doctrines up on the Sufisme discourse, Mahabbah and Ma'rifah. But, the article will be limited by a few verses of Holy Quran that related to the theme.